3D Reconstruction of Human Laryngeal Dynamics Based on Endoscopic High-Speed Recordings - Semmler, Marion; Kniesburges, Stefan; Birk, Veronika; Ziethe, Anke; Patel, Rita; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2016)
Standard laryngoscopic imaging techniques provide only limited two-dimensional insights into the vocal fold vibrations not taking the vertical component into account. However, previous experiments have shown a significant vertical component in the vibration of the vocal folds. We present a 3D reconstruction of the entire superior vocal fold surface from 2D high-speed videoendoscopy via stereo triangulation. In a typical camera-laser set-up the structured laser light pattern is projected on the vocal folds and captured at 4000 fps. The measuring device is suitable for in vivo application since the external dimensions of the miniaturized set-up barely exceed the size of a standard rigid laryngoscope. We provide a conservative estimate on the resulting resolution based on the hardware components and point out the possibilities and limitations of the miniaturized camera-laser set-up. In addition to the 3D vocal fold surface, we extended previous approaches with a G2-continuous model of the vocal fold edge. The clinical applicability was successfully established by the reconstruction of visual data acquired from 2D in vivo high-speed recordings of a female and a male subject. We present extracted dynamic parameters like maximum amplitude and velocity in the vertical direction. The additional vertical component reveals deeper insights into the vibratory dynamics of the vocal folds by means of a non-invasive method. The successful miniaturization allows for in vivo application giving access to the most realistic model available and hence enables a comprehensive understanding of the human phonation process.
EVALuna2:33214